Risk factors of vesicoureteral reflux and urinary tract infections in children with imperforate anus: A population-based case-control study in Taiwan. Issue 44 (5th November 2021) - Wu, Chung-Wei; Wei, Chang-Ching; Lin, Cheng-Li; Chao, Hsiao-Huei; Wei, Tse-Chun; Hsieh, Tsung-Hsueh; Lin, Ching-Yuang
Abstract : Abstract: Imperforate anus (IA) is associated with several urological anomalies, including vesicoureteral reflux (VUR), a major contributor to high morbidity in patients with anorectal malformations. This retrospective study was performed to elucidate the risk factors of vesicoureteral reflux (VUR) and UTI in children with IA. We used the National Health Insurance Research Database (NHIRD) to estimate the frequency of congenital anomalies of the kidney and urinary tract (CAKUT) in children with IA. We also investigated the frequencies of VUR, UTI, and CAKUT in children with IA along with the risk factors of VUR. We enrolled 613 children between 2000 and 2008 (367 males and 246 females; 489 low-position IA and 124 high-position IA). High-position IA was associated with a significantly increased risk of VUR compared with low-position IA (OR: 2.68, 95% CI: 1.61, 4.45). In addition, children with IA along with CAKUT, hydronephrosis, or UTI had a higher risk of VUR (OR: 8.57, 95% CI: 3.75, 19.6; OR: 7.65, 95% CI: 4.48, 13.1; and OR: 31.8, 95% CI: 11.5, 88.3, respectively). UTI, as well as chromosomal anomalies, were more frequent in children with high-position IA. Patients with a high-position IA had a greater risk of VUR, particularly those with CAKUT, hydronephrosis, or UTI. Such patients must periodically undergo urinalysis to screen for UTI and early voiding cystourethrogram to rule out VUR and prevent consequent renal damage. Chromosomal analysis is suggested to rule out Down syndrome.